2016
DOI: 10.1016/j.biopsych.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Administration of the N-Methyl-D-Aspartate Receptor Antagonist Ketamine Improves Rett Syndrome Phenotype

Abstract: Our findings provide strong evidence that targeting NMDA receptors can be a safe and effective treatment for RTT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 72 publications
5
58
0
Order By: Relevance
“…Our study establishes that in Mecp2 KO mice there is an increase of PV expression in both S1 and M1 cortices, similar to what was previously reported in other neocortical areas (Durand et al, 2012; Patrizi et al, 2015; Krishnan et al, 2015, 2017), further highlighting the role of PV regulation in the progression of RTT pathology. Here, we show for the first time that in layer II/III of both S1 and M1 cortices there is an increase in the density of excitatory presynaptic puncta onto dendrites of PV + INs in P28 and P56 Mecp2 KO mice compared with WT littermates.…”
Section: Discussionsupporting
confidence: 91%
“…Our study establishes that in Mecp2 KO mice there is an increase of PV expression in both S1 and M1 cortices, similar to what was previously reported in other neocortical areas (Durand et al, 2012; Patrizi et al, 2015; Krishnan et al, 2015, 2017), further highlighting the role of PV regulation in the progression of RTT pathology. Here, we show for the first time that in layer II/III of both S1 and M1 cortices there is an increase in the density of excitatory presynaptic puncta onto dendrites of PV + INs in P28 and P56 Mecp2 KO mice compared with WT littermates.…”
Section: Discussionsupporting
confidence: 91%
“…Also, the levels of glutamate and the glutamate receptors are increased in patients and mouse models with RTT, contributing to the neuronal hyperexcitability. Interestingly, exposure to the NMDA receptor antagonist ketamine alleviated the RTT-like phenotypes in RTT mouse models, which may be related to disinhibition by presynaptic GABAergic neurons (Patrizi et al, 2016). …”
Section: Abnormities In Neurotransmitter Systemsmentioning
confidence: 99%
“…In this issue, Mierau et al (5) and Patrizi et al (6) provide further evidence for dysregulation of NMDAR expression (5) and the therapeutic potential of ketamine (6) in mouse models of RTT. Previously, the Fagiolini laboratory reported that loss of Mecp2 is associated with hyperinnervation of pyramidal neurons by gamma-aminobutyric acidergic inhibitory interneurons in visual cortex and postweaning regression in visual acuity.…”
mentioning
confidence: 96%
“…In Patrizi et al (6), the authors provide important new information on the therapeutic potential of ketamine in RTT by demonstrating that prolonged treatment of preweaning or postweaning Mecp2 nulls—with the same subanesthetic dose of ketamine used acutely in the Kron et al study (3) (8 mg/kg) —significantly improves visual cortical function and extends lifespan. Possible improvements in other symptoms, including paw clasping and respiration, were also reported but are less clear, as statistical comparisons among saline- and drug-treated mutants are not described.…”
mentioning
confidence: 99%
See 1 more Smart Citation